2010
DOI: 10.1111/j.1834-7819.2010.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of medical emergencies in dental practice: development and evaluation of an undergraduate training programme

Abstract: Background:The evidence available suggests that many dentists on graduation do not feel competent managing medical emergencies; a problem requiring improved undergraduate training. This study developed a comprehensive simulation based training programme for final year undergraduate dental students and assessed student attitudes towards training. Methods: Final year dental students (n = 52) from The University of Melbourne were required to complete simulation training incorporating an interactive tutorial and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 19 publications
(26 reference statements)
2
34
0
2
Order By: Relevance
“…However, as it has been shown with other health professionals, training on high-fidelity simulator is an excellent complement to theoretical training but does not replace it. 25,26 In conclusion, high-fidelity training improves the technical and non-technical skills of dental students for the management of medical emergencies in a dental office. It should therefore be systematically introduced in their curricula.…”
Section: Discussionmentioning
confidence: 92%
“…However, as it has been shown with other health professionals, training on high-fidelity simulator is an excellent complement to theoretical training but does not replace it. 25,26 In conclusion, high-fidelity training improves the technical and non-technical skills of dental students for the management of medical emergencies in a dental office. It should therefore be systematically introduced in their curricula.…”
Section: Discussionmentioning
confidence: 92%
“…After Jarabak's article published in 1968, 20 Tan and Brooks-Buza et al described the use of human patient simulators in emergency training in pediatric advanced dental education, 21,22 and Newby et al and Tanzawa et al described simulation emergency training in predoctoral dental education. 23,24 These studies used student or resident questionnaires to assess educational utility and reported student responses in support of simulation training in emergency management education. Kalsi et al's survey study of emergency simulation training for oral and maxillofacial surgery residents found improvements in personal limitations, recognition of critical illness, communication, assessing acutely ill patients, initiating treatment, and BLS skills.…”
Section: Resultsmentioning
confidence: 99%
“…[526] An earlier study done on the final year dental students toward the development and evaluation of their undergraduate training program reported that realistic simulation training in management of medical emergencies for dental students is an effective adjunct to traditional lecture style teaching. [10] Simulation training was reported to improve the ability to manage medical emergencies. [27] Another study also reported that the more advanced the simulation is the better management of medical emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…[46789] Many of the dentists on graduation have been reported not to feel competent managing medical emergencies[10] and a comprehensive simulation based training program for final year dental students has been advocated. [10] There is a tendency for some dental schools to concentrate on theoretical training while not paying attention to the practical aspect. This lack of uniformity in the dental student's training on medical emergency has also been reported.…”
Section: Introductionmentioning
confidence: 99%